2010
DOI: 10.3109/00016489.2010.506653
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the fossa olfactoria using cone beam tomography (CBT)

Abstract: Surgical procedures in Keros type III where the height of the lateral lamella is much longer than in type II or type I, with an angle of nearly 107° between the lateral lamella and the cribriform plate, are expected to be safer in comparison with Keros type II with 116° and Keros type I with 131°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 16 publications
5
40
0
3
Order By: Relevance
“…Recently, Dahmani-Causse et al assessed the accuracy of MDCT and CBCT for the measurement of footplate thickness [3]; CBCT was associated with more accurate histological measures and theoretical values. Guldner et al defined dehiscence of the bony canal of the internal carotid artery as a bone defect [0.3 mm [7]; the variation rate was 2.7 % in their study of 580 preoperative CBCT scans, which accords with previous MDCT data [4,14] (Table 4).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Recently, Dahmani-Causse et al assessed the accuracy of MDCT and CBCT for the measurement of footplate thickness [3]; CBCT was associated with more accurate histological measures and theoretical values. Guldner et al defined dehiscence of the bony canal of the internal carotid artery as a bone defect [0.3 mm [7]; the variation rate was 2.7 % in their study of 580 preoperative CBCT scans, which accords with previous MDCT data [4,14] (Table 4).…”
Section: Discussionsupporting
confidence: 73%
“…bone is excellent (allowing for detailed study of the anatomy and ventilation air cavities) has been demonstrated previously [2,7]. In CBCT systems, the X-ray beam forms a conical geometry between the source and the detectors; in addition, digital flat-panel detectors replace the row(s) of detectors in conventional CT or MDCT.…”
mentioning
confidence: 94%
“…The accuracy of CBCT has been approved for the assessment of the anterior skull base, olfactory tract, upper airway, and paranasal sinuses [26,27,28]. The overall rate of pathologic findings in maxillary sinus detected by CBCT scanning was reported to be 56.3% by Ritter et al [29], with mucosal thickening being the most frequent pathology (38.1%), followed by partial calcification, opacification, and polypoidal mucosal thickening.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of detecting anatomic variations could already be shown in the paranasal sinuses and temporal bone [3][4][5]. The actual role of the CBT as a diagnostic tool in ENT surgery is until now not completely established.…”
Section: Introductionmentioning
confidence: 97%